2011
DOI: 10.1159/000326072
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating in vitro Tape Stripping: Application of Infrared Densitometry for Quantification of Porcine Stratum Corneum Proteins

Abstract: Infrared (IR) densitometry is a highly practical method recently proposed for protein analysis during in vivo tape stripping. However, this method has not yet been validated for the quantification of porcine stratum corneum (SC) proteins. Therefore, the aim of this study was to establish calibration curves for the analysis of adhesive tapes removed from porcine ear skin. To this end, the protein absorption (as determined via IR densitometry) was correlated with the protein content determined with the Micro BCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 56 publications
4
59
0
Order By: Relevance
“…The absence of 20 crystalline drug in the spectra following delivery in DMSO may be related to the sensitivity of the ATR-FTIR spectroscopy. From the drug extraction profiles ( Figure 7), drug content in each tape strip following application in DMSO is generally below 0.5 µg/cm 2 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The absence of 20 crystalline drug in the spectra following delivery in DMSO may be related to the sensitivity of the ATR-FTIR spectroscopy. From the drug extraction profiles ( Figure 7), drug content in each tape strip following application in DMSO is generally below 0.5 µg/cm 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The amount of sodium hydroxide was four times the quantity previously used to extract protein from porcine SC for an area of ~ 4 cm 2 using D-Squame ® and Corneofix ® tapes [20]. These vials were then shaken at 37ºC for 1 h and sonicated for 30 -60 min at room temperature to fully extract the proteins.…”
Section: Bradford Protein Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies are applying infrared densitometry (IR-D) to in vitro tape stripping using SquameScan TM 850A [3] to verify the endpoint of tape-stripping, i.e., complete SC removal. In fact, the SC depth can be extrapolated from the IR-D data of sequential tape-strips, where the protein content of each tape strip can be indirectly quantified from the tape absorbance [41]; the lower limit of quantification of IR-D indicates the complete removal of the SC (less than 5% of the total SC remaining) and can be used to know the exact numbers of tapes needed. Haque and co-workers [3] investigated the behavior of three UV-filters with different chemical-physical characteristics (BMZ, DHHB and IPMC) using full thickness pig-ear-skin and found that, at the end of the permeation study (12 h), most of the applied dose was recovered in the first five tape strips and none of the sunscreens was detected in the receiving phase.…”
Section: In Vitro Methodsmentioning
confidence: 99%
“…NIR densitometry is an alternative to established methods such as protein quantification on each tape and gravimetric or other optical methods [9,10,11,12]. For human skin in vivo and pig skin in vitro it was established that the NIR pseudoabsorption, measured as the intensity reduction of a circular infrared (IR) laser beam (wavelength 850 nm), is correlated to the amount of protein per area (wt/A) [7,13]:…”
Section: Introductionmentioning
confidence: 99%